LEGAL PROTECTION OF CHILDREN AS PERPETRATORS OF NARCOTICS CRIMES AS AN EFFORT TO REFORM THE LEGAL SYSTEM IN INDONESIA (Study Decision Number: 18/Pid.Sus-Anak/2023/PN.Bnj) - Diana Gultom; Mhd. Azhali Siregar (Yayasan Multidimensi Kreatif, 2025)
The involvement of children in narcotics crimes who become narcotics couriers is a series of malicious agreements in carrying out illegal narcotics trafficking, but in the capacity of the category of children who help in terms of trade or distribution by accompanying the owner of the goods by being promised or lured has often hit children of that age, this is a very concerning thing where the child has been dealt with and are classified as having committed narcotics crimes. In this case, the child has committed an act, malicious consensus without rights or against the law offering to sell, sell, buy, receive, become an intermediary in the sale and purchase, exchange or hand over Class I Narcotics which in the form of plants weighing more than 1 (one) kilogram or exceeding 5 (five) tree trunks or in non-plant forms weighing more than 5 (five) grams. As a result of this incident, the child was charged as regulated and threatened with criminal punishment in Article 114 Paragraph (2) Jo Article 132 paragraph (1) of Law Number 35 of 2009 concerning Narcotics Jo Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The type of research in writing this thesis is carried out with a type of normative legal research in the form of literature research that uses 3 legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. This legal research focuses on literature studies which means that more will be studied and reviewed existing and applicable legal rules. The results of this study show that the Legal Protection of Children as Intermediaries in the Legal System in Indonesia in Decision Number: 18/Pid.Sus-Anak/2023/PN.Bnj. namely by referring to Article 114 Paragraph (2) Jo Article 132 paragraph (1) of Law Number 35 of 2009 concerning Narcotics Jo Law Number 11 of 2012 concerning the Child Criminal Justice System, Legally and convincingly proven guilty of committing a criminal act